A novel strategy of radiofrequency hyperthermia (neothermia) in combination with preoperative chemoradiotherapy for the treatment of advanced rectal cancer: a pilot study. (9th February 2015) - Shoji, Hisanori; Motegi, Masahiko; Osawa, Kiyotaka; Okonogi, Noriyuki; Okazaki, Atsushi; Andou, Yoshitaka; Asao, Takayuki; Kuwano, Hiroyuki; Takahashi, Takeo; Ogoshi, Kyoji
<x xml:space="preserve">Abstract</x> The standardization of radiofrequency hyperthermia using an 8 MHz radiofrequency capacitive heating device can be established as a potential new treatment for rectal cancer concomitant with chemoradiation therapy. This new combined modality provides another potential treatment in patients with rectal cancer.